Juridical Analysis of the Determination of Suspects and Asset Recovery Efforts at the Lebong Resort Police (Case Study on the Investigation of Corruption Crimes PIID-PEL in Sukau Kayo Village, Lebong Atas District, Lebong Regency, Fiscal Year 2019) - Ikhram Nur Azan (Dinasti Research, 2026)
The investigation process of the corruption case of the Pilot Incubation of Village Innovation-Local Economic Development (PIID-PEL) in Sukau Kayo Village for the 2019 Fiscal Year has established three suspects and seized cash amounting to Rp.71,000,000 (seventy-one million rupiah). The objectives of this research are: (1). To understand the process of evaluating evidence to determine suspects in corruption cases, and (2). To understand how investigators from the Anti-Corruption Unit of the Lebong Police Criminal Investigation Unit attempt to recover assets from corruption in the investigation of the PIID-PEL activities of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia in Lebong Atas District, Lebong Regency, Fiscal Year 2019. The type of research is empirical research. Using qualitative methods. Data collection was conducted thru in-depth interviews and secondary data collection. The results of this study show: (1) The process of evaluating evidence to establish a suspect in this case is carried out by investigators and assistant investigators who assess 4 (four) pieces of evidence in the form of witness statements, expert testimony, documents, and the suspect's statement. The evaluation results indicate that the legal subject is reasonably suspected and strongly presumed to have committed a corruption crime. (2) The method used by the Corruption Eradication Unit of the Lebong Police Criminal Investigation Unit in efforts to recover assets from corruption crimes (Asset Recovery) at the investigation stage is by conducting asset tracing, where the results of the asset tracing activities provide information about the flow of money, and the investigator makes efforts to seize the assets.